Improving support for breastfeeding mothers: a qualitative study on the experiences of breastfeeding among mothers who reside in a deprived and culturally diverse community - Erica Jane Cook; Faye Powell; Nasreen Ali; Catrin Penn-Jones; Bertha Ochieng; Gurch Randhawa (BMC, 2021)
Abstract Background The United Kingdom has one of the lowest breastfeeding rates in Europe, with the initiation and continuation of breastfeeding shown to be closely related to the mothers' age, ethnicity and social class. Whilst the barriers that influence a woman's decision to breastfeed are well documented, less is known how these barriers vary by the UK's diverse population. As such, this study aimed to explore mothers' experiences of breastfeeding and accessing breastfeeding services offered locally amongst a deprived and culturally diverse community. Methods A qualitative interpretive study comprising of 63 mothers (white British n = 8, Pakistani n = 13, Bangladeshi n = 10, black African n = 15 and Polish n = 17) who took part in single-sex focus groups, conducted in local community centres across the most deprived and ethnically diverse wards in Luton, UK. The focus groups were audio-recorded, transcribed and analysed thematically using Framework Analysis. Results The most common barriers to breastfeeding irrespective of ethnicity were perceptions surrounding pain and lack of milk. Confidence and motivation were found to be crucial facilitators of breastfeeding; whereby mothers felt that interventions should seek to reassure and support mothers not only during the early stages but throughout the breastfeeding journey. Mothers particularly valued the practical support provided by health care professions particularly surrounding positioning and attachment techniques. However, many mothers felt that the support from health care professionals was not always followed through. Conclusions The findings presented inform important recommendations for the design and implementation of future programs and interventions targeted at reducing breastfeeding inequalities. Interventions should focus on providing mothers practical support and reassurance not only during the early stages but throughout their breastfeeding journey. The findings also highlight the need for tailoring services to support diverse communities which acknowledge different traditional and familial practices.